Hospital Occupational Health Service Network and Reporting Systems in Taiwan From 2008 to 2021. Issue 2 (9th February 2023) - Shih, Ping; Chu, Po-Ching; Huang, Ching-Chun; Guo, Yue Leon; Chen, Pau-Chung; Su, Ta-Chen
Abstract : The study findings have important implications for hospital-based occupational health practices in assessing work-related illnesses and fitness for return to work. Policies that support integrated care may help workers claim compensation and return to work healthily from occupational diseases and injuries. Abstract : Objective: To evaluate the provision of occupational health services at hospitals following the establishment of the Network of Occupational Disease and Injury Service in 2007. Methods: A review of occupational health services during 2008 to 2021 was conducted. The medical practice–based reporting system was compared with the database of compensated occupational diseases (ODs) from Taiwan's Labor Insurance. Results: First-time outpatient visits for occupational evaluation and total visits to Network of Occupational Disease and Injury Service health care institutions increased from 1777 and 9435 to 12, 092 and 23, 210, respectively. Reported ODs increased from 1626 to 2043 with a peak of 2791. Up to 1380 workers evaluated for work resumption in 2021. Similar to the increasing trend in reported ODs, the number of compensated ODs increased over years. Conclusion: The health service needs of Taiwanese workers from OD evaluation to vocational rehabilitation are increasing.